2016
DOI: 10.1007/s11418-016-0992-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening of promising chemotherapeutic candidates from plants extracts

Abstract: Over the course of our studies investigating anti-proliferative properties of compounds originating from plants against human gastric adenocarcinoma (MK-1), human uterine carcinoma (HeLa), murine melanoma (B16F10), and two human T cell lymphotropic virus type 1 (HTLV-1)-infected T-cell lines (MT-1 and MT-2), we have screened 582 extracted samples obtained from a variety of parts from 370 plants. A few extracts showed anti-proliferative activity against all cell lines, but upon further investigation, toxicity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
(40 reference statements)
1
22
0
1
Order By: Relevance
“…Recently, it was shown that calotropin (11) inhibits Wnt signaling by increasing casein kinase 1α in colon cancer cells 19) and 11 induces cell cycle arrest and apoptosis in cisplatinresistant lung cancer cells. 20) In conclusion, as part of our investigations of Asclepiadaceae plants, extracts of A. curassavica showed potent inhibitory effects against MT-1 and MT-2 cell lines. We isolated 17 cardenolides from the extract and examined their structureactivity relationships.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, it was shown that calotropin (11) inhibits Wnt signaling by increasing casein kinase 1α in colon cancer cells 19) and 11 induces cell cycle arrest and apoptosis in cisplatinresistant lung cancer cells. 20) In conclusion, as part of our investigations of Asclepiadaceae plants, extracts of A. curassavica showed potent inhibitory effects against MT-1 and MT-2 cell lines. We isolated 17 cardenolides from the extract and examined their structureactivity relationships.…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, cardenolides are promising candidates for the treatment of ATL, similar to withanolides. 21)…”
Section: Resultsmentioning
confidence: 99%
“…The higher lipophilicity of polyacetylene compounds facilitates plasma membrane penetration but often lowers their bioavailability in vivo (36). A comparison between different plant-derived polyacetylenes by Kinjo et al (46) suggested an inverse relationship of the presence of bulky side chains (hydroxy, methoxy, amino or other groups) with activity and effectiveness. The authors also found that C. intybus polyacetylenes were more effective against MK-1 cells than HeLa and B16F10 cells, and their antiproliferative effects were more profound than other chemoprotective characteristics (46).…”
Section: Antitumor Activity Of the Phytochemicalsmentioning
confidence: 99%
“…A comparison between different plant-derived polyacetylenes by Kinjo et al (46) suggested an inverse relationship of the presence of bulky side chains (hydroxy, methoxy, amino or other groups) with activity and effectiveness. The authors also found that C. intybus polyacetylenes were more effective against MK-1 cells than HeLa and B16F10 cells, and their antiproliferative effects were more profound than other chemoprotective characteristics (46). In estrogen-responsive breast cancer cells (ZR-75-1), both putrescine and spermidine were internalized via the same or similar transporter and both V max was rapidly upregulated by estrogens and insulin (47).…”
Section: Antitumor Activity Of the Phytochemicalsmentioning
confidence: 99%
“…In addition, many cancers still exhibit modest clinical responses to the usual protocols or develop chemotherapy resistance [4]. Thus, in order to achieve more effective and safer molecules, pharmacological studies with substances isolated from plants have been intensified, as well as, synthetic derivatives from these natural compounds [5][6][7].…”
Section: Introductionmentioning
confidence: 99%